SEXUALITY EMERGES IN AFRICA - Gibbs, Andrew (PINS-Psychology in Society, 2025)
Epprecht, M (2008) Heterosexual Africa? The history of an idea from the age of exploration to the age of AIDS. (New African Histories Series edited by Allman, J & Isaacman, A.) Pietermaritizburg: University of KwaZulu-Natal Press; Athens: Ohio University Press. ISBN 978-1-86914-157-8 pbk. Pages xiii + 231. Steyn, M and van Zyl, M (eds) (2009) The prize and the price: Shaping sexualities in South Africa. Cape Town: HSRC Press. ISBN 978-0-7969-2239-7 pbk. Pages viii + 416. Sexuality has, in South Africa and more widely in Africa emerged as an important issue of debate and discussion. In South Africa sexuality emerged as one of the main axes of discussion and contention after the fall of apartheid. As Deborah Posel (2005: 125) wrote, “one of the most striking features of the post-apartheid era has been the politicization of sexuality”. For Posel (2005) the emergence of sexuality as an open area of debate and contention in post-apartheid South Africa (rather than remaining a marginal discourse, regulated by the state and contested at the margins) embodied many of the anxieties of the new South Africa, and threatened the moral and political order: as the nation was born, so it was being undermined through sex and HIV.